Fabrication and electrical response of flexible supercapacitor based on activated carbon from bamboo. Issue 3 (1st March 2017) - Echeverry‐Montoya, N.A.; Prías‐Barragán, J.J.; Tirado‐Mejía, L.; Agudelo, C.; Fonthal, G.; Ariza‐Calderón, H.
Abstract : We present the fabrication and electrical response of a flexible prototype supercapacitor based on activated carbon electrodes obtained from bamboo ( Guadua angustifolia Kunth) as precursor. The supercapacitor prototype was fabricated by using a multilayer configuration method; activated carbon electrodes were impregnated with 0.5 M H2SO4 as electrolyte and filter paper was used as separator. Carbon activation was performed by using NaOH and KOH solutions. Activated carbon electrodes were characterized by adsorption isotherms, cyclic voltammetry, and SEM techniques. Electrical response was found by using charge‐discharge curves. Through adsorption isotherms analysis, we found a surface area of 408 and 309 m 2 g −1 for the activated carbon with NaOH and KOH, respectively. From the electrical characterization analysis of the supercapacitor device, we obtained 0.92 F for the maximum capacitance value by using 0.5 V as fixed value in the bias voltage. Also, we proposed an equivalent electrical circuit for the supercapacitor prototype. This capacitance value is comparable with the capacitance values exhibited by rigid commercial supercapacitor, such as Dinacap and capacitor Capattery Gold, among others. Finally, these results suggest that the activated carbon from bamboo can be used in flexible electronic applications.